Living the Dream: Religion in the (Re)Construction of Sexual Identity in Lesbian, Gay and Bisexual New Zealanders - Henrickson, Mark (Fieldwork in religion, 2012)
Religion and sexuality have been historically uneasy siblings. This large study (n = 2269) examines the role of religion (or no religion) in the construction and living out of gay, lesbian or bisexual identity in Aotearoa New Zealand. The study confirmed that more women consider spirituality important than do men, but that there is significant movement away from Christianity to No Religion. Christian women attain milestone ages later, and demonstrate greater sexual involvement and attraction to men over their lifetimes, and have more children, than do No Religion respondents. Christian men also had longer opposite-sex relationships. Christians were more likely to value, expect and behave exclusively in relationships. Regardless of religiosity, women preferred marriage and men civil unions as the legal recognition of their relationships. The adoption of a life-paradigm by Christian women is considered.